Molecular Epidemiology of Rhodococcus equi of Intermediate Virulence Isolated from Patients with and Without Acquired Immune Deficiency Syndrome in Chiang Mai, Thailand - Takai S. (2014)
We investigated the prevalence of virulent Rhodococcus equi in clinical isolates from 69 sporadic cases (60 men, 8 women, and 1 patient of unknown sex) in Chiang Mai, Thailand, between 1993 and 2001. Fifty were human immunodeficiency virus (HIV) positive, 3 were HIV negative, and HIV status was unknown for 16. Fifty-two (75%) of 69 isolates were strains of intermediate virulence that contained the virulence-associated 20-kDa antigen, and 17 isolates (25%) were avirulent. No virulent strains with the virulence- associated 15-17-kDa antigens were identified. R. equi was isolated from HIV-positive patients' houses and those of their neighbors: avirulent strains were widespread, but only 1 strain of intermediate virulence was isolated. R. equi strains of intermediate virulence were isolated from 4 (0.8%) of 500 submaxillary lymph nodes from apparently healthy pigs in Chiang Mai. The routes of R. equi acquisition should be investigated from the viewpoint of zoonosis and public health.